2007
DOI: 10.1097/brs.0b013e3181316310
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Direct Measurement of Spinal Cord Blood Flow at the Site of Compression

Abstract: Duration of ischemia/compression and blood flow recovery of the spinal cord are important factors in the recovery of motor function after a spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…We found that the SCBF decreased as the spacer size increased immediately after placement of the spacer ( Figure 4 A, B). Although laser Doppler fl owmetry for the CSBF is seldom used in mice, this reduction pattern was consistent with the rat SCBF data reported in a previous study 12 and in our rat model ( Figure 4 C), indicating that our analysis was suffi ciently accurate. At 6 weeks after the spacer placement, the SCBF had fully recovered to the precompression level.…”
Section: Serial Measurement Of Scbf After Spinal Cord Compressionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the SCBF decreased as the spacer size increased immediately after placement of the spacer ( Figure 4 A, B). Although laser Doppler fl owmetry for the CSBF is seldom used in mice, this reduction pattern was consistent with the rat SCBF data reported in a previous study 12 and in our rat model ( Figure 4 C), indicating that our analysis was suffi ciently accurate. At 6 weeks after the spacer placement, the SCBF had fully recovered to the precompression level.…”
Section: Serial Measurement Of Scbf After Spinal Cord Compressionsupporting
confidence: 92%
“…Measurement was carried out using a noncontact probe (1 mm in diameter), the top of which was connected to soft silicone, as described previously. 12 To confi rm the accuracy and reproducibility of our measurements in mice, we also examined the SCBF of Sprague-Dawley rats (280-300 g, female), which has been measured repeatedly in many previous experiments. 12 -15 To examine the infl uence of pre-existing and concurrent SCS on the SCBF after SCI, we measured the SCBF at the lesion epicenter and adjacent area in mice with the 3 types of SCS (no SCS [control], pre-existing SCS, and concurrent SCS).…”
Section: Measurement Of Spinal Cord Blood Flowmentioning
confidence: 98%
“…Laser Doppler was a popular, conventional and real time technique for SCBF in previous studies. However, its limited detecting ability was only up to a 3 mm depth of spinal cord [5]. This made it difficult to monitor SCBF in deep spinal cord tissue in large animals.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include hydrogen clearance, radioactive tracer microsphere and laser Doppler flowmetry. However, few studies show perfusion changes in parenchyma of contusive spinal cord in overall views and real-time [5]. …”
Section: Introductionmentioning
confidence: 99%
“…An experimental SCI model allowing simultaneous monitoring of CSF pressure and SCBF would be a valuable tool for investigating the relationships between these two variables. Several models for assessing the effect of SCI on SCBF have been described [12][13][14][15]. Other models characterised by a decrease in the blood supply to the spinal cord have been developed to investigate relationships between SCBF and CSF pressure, but do not involve traumatic SCI [16][17][18].…”
Section: Introductionmentioning
confidence: 99%